Socio-environmental conflicts and the implantation of wind farms in the Brazilian Northeast - Paulino, Sônia Regina; Paz, Amanda Vitoria Silva; Castilho, André Ferreira de; Nascimento, Daniel Bezerra do; Santos, Miguel Quartieri dos; Delatore, Nicole Lorellai Molizane; Teixeira, Renelle Gomes (Sustainability in Debate, 2023)
Wind energy is already quite relevant in the Brazilian electrical matrix, especially when analysing the country’s Northeast region. This expansion of wind sources gained even more strength with the development of renewable sources in an international context of negotiations to reduce greenhouse gas emissions. However, the implementation and operation of wind farms generate significant socio- environmental impacts on the population around these large enterprises. This research analysed academic articles that portray negative socio-environmental impacts caused by the installation and operation of wind farms in the Northeast of Brazil to address the local conflicts resulting from them situations of environmental injustice. A typology of identified conflicts is presented, classified into four categories: economic, water, land and health and wellness, demonstrating a clear scenario of environmental injustice.